2010
DOI: 10.1021/ma902556k
|View full text |Cite
|
Sign up to set email alerts
|

Primary Amine-Functional Benzoxazine Monomers and Their Use for Amide-Containing Monomeric Benzoxazines

Abstract: Amino-functional benzoxazine monomers have been successfully prepared. Several routes have been applied to incorporate amino group into benzoxazine structure. These approaches include reduction of the corresponding nitro-functional benzoxazines and deprotection of protected aminofunctional benzoxazine monomers. Various approaches that allow primary amine groups to be prepared without damaging the existing benzoxazine groups have been evaluated. Tetrachlorophthalimide and trifluoroacetyl are found to be suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 92 publications
8
88
0
Order By: Relevance
“…The low temperature peak, on the other hand, obviously reflects the reaction between BOX and amine. This finding is in line with that of Agag et al [13]. On the other hand, neither the amine consumption nor the related reaction were studied in detail.…”
Section: Morphology Inspectionsupporting
confidence: 87%
See 1 more Smart Citation
“…The low temperature peak, on the other hand, obviously reflects the reaction between BOX and amine. This finding is in line with that of Agag et al [13]. On the other hand, neither the amine consumption nor the related reaction were studied in detail.…”
Section: Morphology Inspectionsupporting
confidence: 87%
“…A twostep reaction was proposed also for a special BOX end capped EP cured by aromatic diamine (diamino diphenyl sulphone) [12]. In a very recent paper Agag et al [13] reported on the preparation of primary amine-functionalized BOXs and their curing. The differential scanning calorimetric (DSC) thermogram of the primary amine-functionalized BOX showed multiple exotherms above the melting and below the polymerization temperature of the corresponding BOX compound, which can only be assigned to reactions between the oxazine and primary amine (-NH 2 ) groups.…”
Section: Introductionmentioning
confidence: 99%
“…The thermograms show that the maxima of the ring-opening polymerization of pAI-a and oAI-a centered at 219 and 215°C, respectively. The polymerization behavior of amide containing benzoxazines further support our previous finding that the presence of amide (-NH-CO-) linkage accelerated the polymerization in comparison with ordinary benzoxazines (Agag et al, 2010).…”
Section: Polymerization Behavior Of Benzoxazine Monomerssupporting
confidence: 86%
“…Thus, polybenzoxazine can satisfy specic requirements for different applications such as high temperature resistant adhesives, coatings, membranes and aerospace materials. For example, the thermal stability of polybenzoxazines can be achieved by incorporation of various functionalities such as amide, 16,17 and furfuryl 22 or increasing the number of oxazine rings in molecular backbone. 23 Benzoxazines containing hydroxyl group have been extensively studied due to their lower polymerization temperature and the modiable character of hydroxyl functionality.…”
Section: Introductionmentioning
confidence: 99%